Modeling of Electromagnetic Fields of the Traction Network Taking into Account the Influence of Metal Structures - Iliya Iliev; Andrey Kryukov; Konstantin Suslov; Ekaterina Voronina; Andrey Batukhtin; Ivan Beloev; Yuliya Valeeva (Applied Sciences, 2025)
The paper addresses the issues of electromagnetic safety in traction networks of 25 kV AC railways. The purpose of the research is to develop digital models to determine the strengths of electromagnetic fields (EMFs) created by traction networks near portal-type metal structures. Such a structure in this study is represented by an overpass located above the tracks. The presence of a conductive structure significantly complicates the picture of EMF distribution in space. In contrast to the plane-parallel EMF of the traction network on interstation tracks in the spans between the supports of the catenary system, the field in this situation becomes three-dimensional. The technology for detecting strength relies on the concept of segments of limited length conductors, some of which may be buried. In order to apply the quasi-stationary zone equations to frequencies of up to 2000 Hz, it is essential to ensure that the size of the set of objects composed of these conductors does not exceed several hundred meters. Based on the modeling results, the dependences of the amplitudes and components of EMF strengths on the z-coordinate passing along the axis of the railway were obtained. In addition, three-dimensional diagrams were constructed to analyze the distribution of EMF in space. The findings of the studies show that the presented technique allows considering the influence of metal structures when modeling the electromagnetic fields of traction networks. It can be used in practice to develop effective measures to enhance electromagnetic safety conditions.